Assessing local cultural awareness in university EFL learners: A Delphi and AHP-based index framework - Lunan Fan; Guiping Cheng; Na Yan (PLoS ONE, 2025)
To address the neglect of local cultural identity in university EFL learners’ development, this study has developed and validated an evaluation framework for assessing their cultural awareness, with direct implications for curriculum reform. The framework operationalizes Kramsch’s symbolic competence theory and Byram’s ICC principles into measurable dimensions, achieved through two rounds of Delphi consultations with 15 EFL education experts (Kendall’s W = 0.86, p < 0.01) and one round of Analytic Hierarchy Process (AHP) analysis (consistency ratios < 0.1). The finalized index system comprises three primary dimensions—Local Expression and Application (45.27%), Local Affective Attitudes (33.01%), and Local Cognition and Understanding (21.72%)—alongside 18 secondary indicators. Key innovations include balancing cultural pride and cross-cultural openness at identical weights (0.1181) and integration with CEFR/ACTFL via descriptor mapping (e.g., mapping local storytelling to CEFR C1 “pluricultural mediation”). This framework equips educators, curriculum developers, and policymakers with practical tools to design culturally grounded assessments and curricula, advancing a shift beyond Anglophone-centric models.